(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
This work is devoted to the study of the reasons for the company’s IPO. Based on the bibliographic analysis, several reasons for the company’s IPO were listed and the answer to the question “Why is going public so important” was received.